Immigrants' Deportations, Local Crime and Police Effectiveness - Annie Laurie Hines; Giovanni Peri (Institute of Labor Economics (IZA), 2019)
This paper analyzes the impact of immigrant deportations on local crime and police efficiency. Our identification relies on increases in the deportation rate driven by the introduction of the Secure Communities (SC) program, an immigration enforcement program based on local-federal cooperation which was rolled out across counties between 2008 and 2013. We instrument for the deportation rate by interacting the introduction of SC with the local presence of likely undocumented in 2005, prior to the introduction of SC. We document a surge in local deportation rates under SC, and we show that deportations increased the most in counties with a large undocumented population. We find that SC-driven increases in deportation rates did not reduce crime rates for violent offenses or property offenses. Our estimates are small and precise, so we can rule out meaningful effects. We do not find evidence that SC increased either police effectiveness in solving crimes or local police resources. Finally, we do not find effects of deportations on the local employment of unskilled citizens or on local firm creation.
Keywords: K24; K37; 330; immigrants; deportation; crime; police effectiveness; secure communities